Piezoelectric ceramic preparation method capable of obtaining piezoelectric property without polarization

By covering the ZSO nanofilm on the surface of the PZT-based ceramic powder, using the compressive stress generated by the ZSO phase transition, the piezoelectric performance is achieved without polarization, and the piezoelectric ceramics need to be polarized in the prior art to obtain piezoelectric electricity. The performance problem significantly improves the stability of piezoelectric performance.

CN119462142APending Publication Date: 2025-02-18CHANGZHOU UNIV
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411673978.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Existing piezoelectric ceramic materials require high voltage polarization to obtain piezoelectric properties, but this process is complex and there is a risk of depolarization, resulting in unstable piezoelectric properties.

Method used

By uniformly covering the ZSO nanofilm on the surface of the PZT-based ceramic powder, the compressive stress generated by the ZSO phase transition is used to induce the piezoelectric effect, and piezoelectric performance is achieved without polarization.

Benefits of technology

This method avoids the risk of high temperature, electric field and impact during polarization, significantly reduces the possibility of depolarization, and makes the piezoelectric properties obtained by piezoelectric ceramics more stable and lasting.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119462142A_ABST
    Figure CN119462142A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of application of lead-based piezoelectric ceramics, and particularly relates to a preparation method of piezoelectric ceramics capable of obtaining piezoelectric property without polarization. The surface of PZT-BZnI powder is uniformly coated with a nano film ZSO through an oil-phase nano reactor, the PZT-based piezoelectric ceramic is prepared through solid-phase reaction, rapid sintering and rapid cooling, the phase change of the ZSO occurs in the rapid cooling process, pressure stress with proper size and uniform distribution is generated at the grain boundary of the PZT-based ceramic, the piezoelectric effect is induced, and the piezoelectric ceramic can directly obtain the piezoelectric property without polarization. The oil-phase nano-reactor has the advantages that the surface of the lead-based powder is uniformly coated with the nano-film, and the defects that an existing core-shell structure is complex in preparation process and uneven in distribution are overcome; the uniformly coated nano-film ZSO generates lasting and uniform pressure stress through phase change, so that the piezoelectric property of the lead-based piezoelectric ceramic is obtained without polarization, and depolarization is avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lead-based piezoelectric ceramics, and in particular to a method for preparing piezoelectric ceramics that can obtain piezoelectric properties without polarization. Background Art

[0002] Piezoelectric ceramics are polycrystalline materials that can realize the mutual conversion between electrical quantity and mechanical quantity, electrical energy and mechanical energy. They are used to prepare drivers and transducers and are widely used in high-tech fields such as electronic information, national defense science and technology, and biomedicine.

[0003] Due to the formation of electric domain structures in polycrystalline ceramics, piezoelectric ceramics do not exhibit piezoelectric effect and need to be polarized to obtain piezoelectric properties. Existing high-voltage DC polarization and newer AC polarization and pulse polarization methods require expensive equipment such as high-voltage power supplies and pulse signal sources, adding additional material processing processes, and there is a risk of depolarization caused by high temperature, electric field, impact, etc., thereby losing piezoelectric properties. Therefore, it is necessary to develop a material preparation method that does not require polarization and allows piezoelectric ceramics to directly obtain piezoelectric properties.

[0004] Stress-induced ferroelectric domain orientation provides a way to obtain piezoelectric properties in piezoelectric ceramics without polarization. 2 The high and low temperature crystal transformation has a large volume effect and can introduce compressive stress. The present invention forms a uniformly coated nanofilm on the surface of the piezoelectric powder through an oil phase nanoreactor, controls the volume effect by introducing a small amount of Sr element, and realizes the high and low temperature crystal transformation through rapid sintering and rapid cooling, providing a new idea of ​​introducing a compressive stress of appropriate size and uniform distribution at the grain boundary of piezoelectric ceramics, which can avoid the explosion of ceramic sintering process and enable piezoelectric ceramics to directly obtain piezoelectric properties without polarization.

[0005] Lead zirconate titanate (Pb(ZrTi)O 3 ) is the main material of commercial piezoelectric drivers and transducers. The present invention introduces a small amount of Bi-based second component, which can appropriately reduce the sintering temperature, reduce the compressive stress caused by the high and low temperature crystal transformation during the rapid cooling process, avoid ceramic cracking during the sintering process, and improve the sintering yield.

[0006] The information disclosed in this background technology section is only intended to deepen the understanding of the overall background technology of the present invention, and should not be regarded as acknowledging or suggesting in any form that the information constitutes the prior art known to those skilled in the art. Summary of the invention

[0007] The purpose of the present invention is to provide a method for preparing piezoelectric ceramics by forming a core-shell structure through rapid sintering and rapid cooling of an oil-phase nanoreactor, wherein a piezoelectric effect is induced in a PZT-based ceramic by means of ZSO phase change stress through uniform coating of a nanofilm in an oil-phase nanoreactor in combination with rapid sintering and rapid cooling, so that the piezoelectric ceramics can obtain piezoelectric properties without polarization.

[0008] The above technical objectives of the present invention are achieved through the following technical solutions:

[0009] A method for preparing a piezoelectric ceramic that does not require polarization to obtain piezoelectric properties comprises the following steps:

[0010] S1: PZT-BZnI was prepared by solid phase reaction method, and then ground into submicron powder after calcination;

[0011] S2: The ZSO nanofilm is uniformly coated on the surface of PZT-BZnI powder through an oil phase nanoreactor to form a core-shell structure;

[0012] S3: subjecting the coated core-shell structure to solid phase reaction, rapid sintering and rapid cooling to prepare PZT-based piezoelectric ceramics;

[0013] Among them, the ZSO phase change stress induces the piezoelectric effect, which enables the piezoelectric ceramics to obtain piezoelectric properties without polarization.

[0014] Specifically, the present invention uses an ultrasonic cell crusher for high-energy stirring to ensure that the ZSO precursor is evenly distributed in the oil phase. In this way, the ZSO precursor can be evenly coated on the surface of the PZT-BZnI powder at the nanoscale. During the reaction, the temperature (70-80°C) and the reaction time (4h) are controlled and carried out under nitrogen protection to avoid overreaction or insufficient deposition, so that ZSO can be evenly coated on the surface of the PZT-BZnI powder. On this basis, the molar ratio of ZSO to PZT-BZnI is controlled at 1.5-2.5mol% to obtain an appropriate coating thickness. Too little ZSO cannot be completely coated, and too much ZSO is easy to form agglomerates on the surface of the powder, affecting the piezoelectric properties.

[0015] During the rapid sintering and rapid cooling process, ZSO transforms from a tetragonal phase to a monoclinic phase. This phase change causes changes in the lattice structure, resulting in compressive stress. This stress is evenly transferred to the PZT matrix in the sintered PZT grains, thereby forming a persistent and uniform stress field inside the ceramic. This uniform stress field can induce the dipoles in the PZT matrix to be arranged in a specific direction. Even without external electric field polarization, since the phase change stress of ZSO is endogenous and evenly distributed, a persistent electric dipole moment is formed inside the piezoelectric ceramic. This enables the piezoelectric ceramic to obtain piezoelectric properties without polarization.

[0016] As a preferred embodiment, the chemical formula of PZT-BZnI is (1-x)Pb(Zr 0.5 Ti 0.5 ) 3 -xBi(Zn 0.5 Ir 0.5 ) 3, x=0.025-0.075, the present invention introduces BZnI into PZT and utilizes the low melting point of BZnI to promote the diffusion rate during the sintering process, so as to appropriately reduce the sintering temperature of PZT ceramics. The doping of BZnI improves the density and uniformity of the grains on the one hand, and optimizes the crystal phase structure on the other hand, thereby ensuring that the piezoelectric performance will not be significantly reduced due to the reduction of the sintering temperature. The composition selection takes into account both the appropriate reduction of the sintering temperature and the maintenance of certain piezoelectric performance. Submicron PZT-BZnI powder can improve the density and uniformity of ceramics. Smaller powder size helps to reduce pores during the sintering process and obtain higher ceramic density.

[0017] Preferably, the preparation method of PZT-BZnI is:

[0018] According to the chemical formula (1-x)Pb(Zr 0.5 Ti 0.5 ) 3 -xBi(Zn 0.5 Ir 0.5 ) 3 The analytically pure oxide raw materials after sufficient drying are accurately weighed, mixed evenly, and calcined at 860-840° C. for 2 h; the calcined PZT-BZnI is crushed and ground with a colloid mill, the colloid mill speed is 4000 rpm, the water cooling pressure is 0.2 MPa, the wet three-stage grinding is performed, the flow rate is 1 L / h, and submicron PZT-BZnI powder is obtained after drying.

[0019] As a preferred analytically pure oxide raw material includes: PbO, ZrO 2 、TiO 2 、Bi 2 O 3 , ZnO and Ir 2 O 3 .

[0020] As a preferred embodiment, the chemical formula of ZSO is Zr 0.9 Sr 0.1 O 2 . The compressive stress generated by the phase change of ZSO can stably induce piezoelectric properties, so that no additional polarization process is required. This means that the prepared piezoelectric ceramics are not easily affected by the external environment (such as high temperature or mechanical stress) and depolarized, which enhances the long-term stability of the piezoelectric properties. The use of oil-phase nanoreactors to prepare ZSO is simple and efficient. Compared with the traditional core-shell structure preparation process, the oil-phase nanoreactor can better control the uniform coating of ZSO on PZT-BZnI powder, and the process steps are simple and highly repeatable.

[0021] Preferably, step S2 includes:

[0022] S21: Accurately weigh ZrOCl according to the stoichiometric ratio 2 8H 2 O、SrCl 2 Put it into the ethanol-cyclohexane mixture, add acrylamide, and use ultrasonic cell crusher to stir with high energy to prepare oil phase nanoemulsion;

[0023] In this process, a mixture of ethanol and cyclohexane is used and acrylamide is added to form a stable oil phase nanoemulsion. The mixture of ethanol and cyclohexane allows polar and non-polar environments to coexist, which is conducive to the formation of a uniformly dispersed nanoreactor environment. Acrylamide as a surfactant can further reduce the interfacial tension, so that the ZSO precursor can be evenly distributed at the nanoscale. High-energy stirring is performed by an ultrasonic cell crusher. The power of the device is 250W, and the pulse stirring is performed. After stirring for 15 seconds, stop for 1-2 seconds, and then stir for another 15 seconds. The total stirring time is 3-5 minutes, which can make the precursor material better dispersed in the oil phase, thereby ensuring that the final oil phase nanoemulsion has good uniformity. This uniformity is crucial for the subsequent coating process.

[0024] S22: Weigh the PZT-BZnI powder and add it to the above emulsion, heat it in a water bath at 70-80°C under nitrogen protection, and react for 4 hours to obtain a ZSO nanofilm uniformly coating the PZT-BZnI powder. The reaction is carried out under nitrogen protection, avoiding oxidation reactions that may be caused by the presence of oxygen, ensuring the chemical stability and purity of the coating material, and improving the coating quality.

[0025] The present invention ensures the sufficiency and stability of the reaction by controlling the reaction temperature at 70-80°C for 4 hours. A higher temperature can accelerate the coating of the ZSO precursor on the surface of the PZT-BZnI powder, while controlling the reaction time to avoid overreaction, ensuring uniform coating without agglomeration; using water bath heating can make the temperature of the entire system uniform, which is conducive to uniformly coating the nanofilm on the surface of the PZT-BZnI powder and improving the adhesion and stability of the ZSO film.

[0026] In the present invention, (1-x)Pb(Zr 0.5 Ti 0.5 ) 3 -xBi(Zn 0.5 Ir 0.5 ) 3 and Zr 0.9 Sr 0.1 O 2 In specific experiments, accurate weighing with a 1 / 10,000 balance can ensure the accurate ratio between the reactants, ensure that the chemical composition remains consistent during the preparation process, and avoid component deviations that lead to poor coating effects or unstable performance.

[0027] Preferably, in the ethanol-cyclohexane mixture, the volume ratio of ethanol:cyclohexane is 1:1, and acrylamide is used as a surfactant, generally accounting for about 3 wt% of the total mass of the liquid.

[0028] Preferably, in step S22, the amount ratio of ZSO coating PZT-BZnI is: ZSO:PZT-BZnI=1.5-2.5 mol%, that is, ZSO accounts for 1.5-2.5 mol% of PZT-BZnI. ZSO can form a good coating within this range. Too little ZSO cannot be completely coated, and too much ZSO will agglomerate, affecting the piezoelectric properties of the piezoelectric ceramic.

[0029] Preferably, step S3 includes:

[0030] The obtained ZSO-coated PZT-BZnI was calcined at 390-410°C, and then polyvinyl alcohol was added to granulate and tablet. The binder was debinded at 600°C. The debinded blank was rapidly sintered and rapidly cooled in an air atmosphere to prepare PZT-based ceramics. The rapid sintering temperature was 1215-1195°C and the sintering time was 20-40min. After sintering, it was directly cooled to room temperature.

[0031] Among them, calcining the ZSO-coated PZT-BZnI powder at 390-410°C can effectively remove the residual organic matter and impurities in the precursor synthesis process, ensure the purity of the powder, and the calcination process can promote the bonding between the ZSO coating layer and the PZT-BZnI powder, improve the stability of the material, and prepare for the subsequent sintering process. Adding polyvinyl alcohol (PVA) granulation helps to improve the fluidity and molding properties of the powder, ensure the formation of dense and uniform blanks during the tableting process, and thus improve the density of subsequent sintering. Tabletting can make the particles evenly distributed and improve the density, reduce the generation of voids, and ensure that high-density ceramics are obtained in the subsequent sintering process. After that, the debinding treatment at 600°C can completely remove the polyvinyl alcohol added during the granulation process to avoid defects caused by residual organic matter during the sintering process.

[0032] The present invention focuses on fast sintering and fast cooling of ZSO to achieve phase change, wherein the fast sintering temperature is high and the time is short, and the high sintering temperature promotes the effective sintering of grains, and a high-density piezoelectric ceramic can be obtained; densification is completed in a short time, and excessive growth of grains caused by long-term high temperature is avoided, which helps to maintain a small and uniform grain size, thereby improving the mechanical and electrical properties of the material; and fast sintering is conducive to stabilizing the core-shell structure, avoiding excessive diffusion of ZSO into the grains, and stabilizing the compressive stress generated at the grain boundary. Rapid cooling can effectively retain the phase structure formed during the sintering process, prompting ZSO to undergo phase change, generate internal stress and solidify. These internal stresses help to form a lasting polarization effect in the ceramic, forming stable piezoelectric properties, so that the ceramic can obtain piezoelectric properties without polarization. On this basis, it can also prevent lattice relaxation and depolarization caused by slow cooling, making the piezoelectric performance more stable.

[0033] By means of the above technical solution, the present invention has at least the following beneficial effects:

[0034] Conventional piezoelectric ceramics may depolarize due to external factors (such as temperature changes or mechanical shocks) after polarization. In the present invention, the internal stress generated by the ZSO phase transition forms a stable structure inside the ceramic, avoiding the influence of the external environment on the piezoelectric properties, thereby significantly reducing the possibility of depolarization. This persistent uniform stress is solidified in the ceramic structure during the sintering process, and the piezoelectric properties are more stable than those generated by polarization. The obtained lead-based piezoelectric ceramics can obtain piezoelectric properties without polarization and will not depolarize.

[0035] The present invention uses an oil phase nanoreactor to uniformly coat a nanofilm ZSO on the surface of a PZT-BZnI powder to form a core-shell structure, thereby overcoming the shortcomings of the existing core-shell structure, such as complex preparation process and uneven distribution. On this basis, a PZT-based piezoelectric ceramic is prepared by solid phase reaction, rapid sintering and rapid cooling. The nanofilm ZSO is uniformly coated in the rapid sintering and rapid cooling process, and undergoes phase change from a tetragonal phase to a monoclinic phase, thereby generating persistent uniform stress. A small amount of Sr is added in the present invention to slightly reduce the phase change stress, thereby achieving performance regulation. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0037] Figure 1 This is a resonance diagram representing the electromechanical coupling coefficient in Example 1 of the present invention. DETAILED DESCRIPTION

[0038] The technical solutions in the embodiments of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.

[0039] The present invention uses an oil phase nanoreactor to uniformly coat the surface of PZT-BZnI powder with a nanofilm ZSO, and prepares PZT-based piezoelectric ceramics through a rapid sintering and rapid cooling process. During the rapid cooling process, ZSO undergoes a phase change, and a compressive stress of appropriate size and uniform distribution is generated at the grain boundary of the PZT-based ceramic, inducing a piezoelectric effect, so that the piezoelectric ceramics directly obtain piezoelectric properties without polarization: the piezoelectric constant d 33 =198-208pC / N, electromechanical coupling coefficient K p =0.291-0.297.

[0040] Example 1

[0041] S1: Preparation of 0.95Pb(Zr) by solid phase reaction method 0.5 Ti 0.5 ) 3 -0.05Bi(Zn 0.5 Ir 0.5 ) 3 (PZT-0.05BZnI), the specific steps are: accurately weigh the fully dried analytical pure PbO and ZrO according to the stoichiometric ratio 2 、TiO 2 、Bi 2 O 3 、ZnO、Ir 2 O 3 , mixed evenly, and calcined at 850℃ for 2h. The calcined PZT-0.05BZnI was crushed and ground with a colloid mill, with a colloid mill speed of 4000rpm, a water cooling pressure of 0.2MPa, a wet three-stage grinding, and a flow rate of 1L / h. After drying, submicron PZT-0.05BZnI powder was obtained.

[0042] S2: Nanofilm ZSO is uniformly coated on the surface of PZT-0.05BZnI through an oil phase nanoreactor. The specific steps are: accurately weigh ZrOCl according to the stoichiometric ratio 2 8H 2 O、SrCl 2Put into an appropriate amount of ethanol-cyclohexane mixed solution (volume ratio of ethanol: cyclohexane = 1:1), add 3wt% acrylamide, and use ultrasonic cell crusher to stir at high energy to prepare oil phase nanoreactor. Weigh an appropriate amount of submicron PZT-0.05BZnI powder and add it to the above emulsion (ZSO: PZT-BZnI = 2mol%, solid content 10wt%), heat in a water bath at 75°C under nitrogen protection, react for 4h, and obtain ZSO nanofilm uniformly coated with PZT-0.05BZnI powder.

[0043] S3: Prepare PZT-based piezoelectric ceramics by rapid sintering and rapid cooling process, the specific steps are: ZSO coated PZT-0.05BZnI is calcined at 400℃, and then an appropriate amount of polyvinyl alcohol is added to granulate and press the pellets, and the binder is removed at 600℃. The blank after debinding is sintered in air atmosphere at a rapid sintering temperature of 1205℃ for 30min, and directly cooled to room temperature after sintering to prepare PZT-based ceramics. The piezoelectric constant d is measured. 33 =198pC / N, electromechanical coupling coefficient K p =0.291.

[0044] Example 2

[0045] S1: Preparation of 0.975Pb(Zr) by solid phase reaction method 0.5 Ti 0.5 ) 3 -0.025Bi(Zn 0.5 Ir 0.5 ) 3 (PZT-0.025BZnI), the specific steps are: accurately weigh the fully dried analytical pure PbO and ZrO according to the stoichiometric ratio 2 、TiO 2 、Bi 2 O 3 、ZnO、Ir 2 O 3 , mixed evenly, and calcined at 860℃ for 2h. The calcined PZT-0.025BZnI was crushed and ground with a colloid mill, with a colloid mill speed of 4000rpm, a water cooling pressure of 0.2MPa, a wet three-stage grinding, and a flow rate of 1L / h. After drying, submicron PZT-0.025BZnI powder was obtained.

[0046] S2: Nanofilm ZSO is uniformly coated on the surface of PZT-0.025BZnI through an oil phase nanoreactor. The specific steps are: accurately weigh ZrOCl according to the stoichiometric ratio 2 8H 2 O、SrCl 2Put it into an appropriate amount of ethanol-cyclohexane mixed solution (volume ratio of ethanol: cyclohexane = 1:1), add a small amount of acrylamide, and use an ultrasonic cell crusher to stir at high energy to prepare an oil phase nanoreactor. Weigh an appropriate amount of submicron PZT-0.025BZnI powder and add it to the above emulsion (ZSO: PZT-BZnI = 1.5 mol%, solid content 10wt%), heat it in a water bath at 75°C under nitrogen protection, react for 4 hours, and obtain a ZSO nanofilm uniformly coated with PZT-0.025BZnI powder.

[0047] S3: PZT-based piezoelectric ceramics were prepared by rapid sintering and rapid cooling process. The specific steps were as follows: ZSO-coated PZT-0.025BZnI was calcined at 410°C, an appropriate amount of polyvinyl alcohol was added to granulate and press, and the binder was removed at 600°C. The debinding blank was rapidly sintered in air atmosphere at 1215°C for 40 minutes and directly cooled to room temperature after sintering to prepare PZT-based ceramics. The piezoelectric constant d was measured. 33 =203pC / N, electromechanical coupling coefficient K p =0.294.

[0048] Example 3

[0049] S1: Preparation of 0.925Pb(Zr) by solid phase reaction method 0.5 Ti 0.5 ) 3 -0.075Bi(Zn 0.5 Ir 0.5 ) 3 (PZT-0.075BZnI), the specific steps are: accurately weigh the fully dried analytical pure PbO and ZrO according to the stoichiometric ratio 2 、TiO 2 、Bi 2 O 3 、ZnO、Ir 2 O 3 , mixed evenly, and calcined at 840℃ for 2h. The calcined PZT-0.075BZnI was crushed and ground with a colloid mill, with a colloid mill speed of 4000rpm, a water cooling pressure of 0.2MPa, a wet three-stage grinding, and a flow rate of 1L / h. After drying, submicron PZT-0.075BZnI powder was obtained.

[0050] S2: The nanofilm ZSO is uniformly coated on the surface of PZT-0.075BZnI through an oil phase nanoreactor. The specific steps are: accurately weigh ZrOCl according to the stoichiometric ratio 2 8H 2 O、SrCl 2Put it into an appropriate amount of ethanol-cyclohexane mixed solution (volume ratio of ethanol: cyclohexane = 1:1), add a small amount of acrylamide, and use an ultrasonic cell crusher to stir at high energy to prepare an oil phase nanoreactor. Weigh an appropriate amount of submicron PZT-0.075BZnI powder and add it to the above emulsion (ZSO: PZT-BZnI = 2.5 mol%, solid content 10 wt%), heat it in a water bath at 75 ° C under nitrogen protection, react for 4 hours, and obtain a ZSO nanofilm uniformly coated with PZT-0.075BZnI powder.

[0051] S3: PZT-based piezoelectric ceramics were prepared by rapid sintering and rapid cooling process. The specific steps were as follows: ZSO-coated PZT-0.075BZnI was calcined at 390°C, an appropriate amount of polyvinyl alcohol was added to granulate and press, and the binder was removed at 600°C. The debinding blank was rapidly sintered in air at 1195°C for 20 minutes and directly cooled to room temperature after sintering to prepare PZT-based ceramics. The piezoelectric constant d was measured. 33 =208pC / N, electromechanical coupling coefficient K p =0.297.

[0052] The application scope of the present invention is not limited to lead zirconate titanate (Pb(Zr 0.5 Ti 0.5 ) 3 )-based ceramics, and is also applicable to other compositions of lead zirconate titanate (Pb(Zr 1-x Ti x ) 3 ) based ceramics.

[0053] Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A method for preparing a piezoelectric ceramic that does not require polarization to obtain piezoelectric properties, characterized in that: The steps are as follows: S1: PZT-BZnI was prepared by solid phase reaction method, and then ground into submicron powder after calcination; S2: The ZSO nanofilm is uniformly coated on the surface of PZT-BZnI powder through an oil phase nanoreactor to form a core-shell structure; S3: subjecting the coated core-shell structure to solid phase reaction, rapid sintering and rapid cooling to prepare PZT-based piezoelectric ceramics; Among them, the ZSO phase change stress induces the piezoelectric effect, which enables the piezoelectric ceramics to obtain piezoelectric properties without polarization.

2. The method for preparing a piezoelectric ceramic having piezoelectric properties without polarization according to claim 1, characterized in that: In step S1, the chemical formula of PZT-BZnI is (1-x)Pb(Zr 0.5 Ti 0.5 )O3-xBi(Zn 0.5 Ir 0.5 )O3, x=0.025-0.

075.

3. The method for preparing a piezoelectric ceramic having piezoelectric properties without polarization according to claim 2, characterized in that: The preparation method of the PZT-BZnI is: According to the chemical formula (1-x)Pb(Zr 0.5 Ti 0.5 )O3-xBi(Zn 0.5 Ir 0.5 )O3 is accurately weighed and fully dried analytically pure oxide raw materials, mixed evenly, and calcined at 860-840°C for 2h; the calcined PZT-BZnI is crushed and ground with a colloid mill at a speed of 4000rpm, a water cooling pressure of 0.2MPa, three-stage wet grinding, and a flow rate of 1L / h, and submicron PZT-BZnI powder is obtained after drying.

4. The method for preparing a piezoelectric ceramic having piezoelectric properties without polarization according to claim 3, characterized in that: Analytical pure oxide raw materials include: PbO, ZrO2, TiO2, Bi2O3, ZnO and Ir2O3.

5. A method for preparing a piezoelectric ceramic that does not require polarization to obtain piezoelectric properties according to any one of claims 1 to 4, characterized in that: In step S2, the chemical formula of ZSO is Zr 0.9 Sr 0.1 O2.

6. The method for preparing a piezoelectric ceramic having piezoelectric properties without polarization according to claim 5, characterized in that: Step S2 includes: S21: accurately weighing ZrOCl2·8H2O and SrCl2 according to the stoichiometric ratio and putting them into a mixed solution of ethanol and cyclohexane, adding acrylamide, and stirring with an ultrasonic cell pulverizer at high energy to prepare an oil phase nanoemulsion; S22: Weigh PZT-BZnI powder and add it to the above emulsion, heat it in a water bath at 70-80°C under nitrogen protection, and react for 4 hours to obtain a ZSO nanofilm uniformly covering the PZT-BZnI powder.

7. A method for preparing a piezoelectric ceramic that obtains piezoelectric properties without polarization according to claim 6, characterized in that: In the ethanol-cyclohexane mixture, the volume ratio of ethanol:cyclohexane is 1:

1.

8. The method for preparing a piezoelectric ceramic having piezoelectric properties without polarization according to claim 6, characterized in that: In step S22, the ratio of the amount of ZSO coated PZT-BZnI is: ZSO:PZT-BZnI=1.5-2.5 mol%.

9. The method for preparing a piezoelectric ceramic having piezoelectric properties without polarization according to claim 1, characterized in that: Step S3 includes: The obtained ZSO-coated PZT-BZnI was calcined at 390-410°C, and then polyvinyl alcohol was added to granulate and tablet, and the binder was debinded at 600°C. The debinded blank was rapidly sintered and rapidly cooled in an air atmosphere to prepare PZT-based ceramics. The rapid sintering temperature was 1215-1195°C and the sintering time was 20-40min. After sintering, it was directly cooled to room temperature.

Citation Information

Cited By

  • Method and system for optimizing preparation process of high-temperature-resistant polypropylene insulating material

    CN121435547A

  • Method and system for optimizing preparation process of high-temperature-resistant polypropylene insulation material

    CN121435547B